Effect and Regulation of the NLRP3 Inflammasome During Renal Fibrosis - Zhang, Hong; Wang, Zhengchao (Frontiers in Cell and Developmental Biology, 2020)
Renal fibrosis is a common pathological process where certain primary or secondary kidney diseases can continue to progress to the end-stage of these kidney diseases; however, the molecular mechanisms underlying renal fibrosis remain unclear. Recently, research focusing on examining the function of inflammasomes has attracted a great deal of attention, and data derived from these research projects have increased our understanding of the effects and regulation of inflammasomes during renal fibrosis. Based on this, the present review summarizes recent findings in regard to NLRP3 inflammasome functions during various kidney diseases, and these findings indicate that NLRP3 inflammasome not only mediate the inflammatory response, but are also associated with pyroptosis, mitochondrial regulation, and myofibroblast differentiation during renal fibrosis. These novel findings provide us with a more in-depth understanding of the pathogenesis of renal fibrosis and will aid in the identification of new targets that can be used for the prevention and treatment of this disease.